Childhood maltreatment and methylation of the glucocorticoid receptor gene NR3C1 in bipolar disorder. (January 2014) - Perroud, Nader; Dayer, Alexandre; Piguet, Camille; Nallet, Audrey; Favre, Sophie; Malafosse, Alain; Aubry, Jean-Michel
Abstract : Background: Early-life adversities represent risk factors for the development of bipolar affective disorder and are associated with higher severity of the disorder. This may be the consequence of a sustained alteration of the hypothalamic–pituitary–adrenal (HPA) axis resulting from epigenetic modifications of the gene coding for the glucocorticoid receptor ( NR3C1 ). Aims: To investigate whether severity of childhood maltreatment is associated with increased methylation of the exon? 1F NR3C1 promoter in bipolar disorder. Method: A sample of people with bipolar disorder ( n = 99) were assessed for childhood traumatic experiences. The percentage of NR3C1 methylation was measured for each participant. Results: The higher the number of trauma events, the higher was the percentage of NR3C1 methylation (β = 0.52, 95% CI 0.46–0.59, P <<0.0001). The severity of each type of maltreatment (sexual, physical and emotional) was also associated with NR3C1 methylation status. Conclusions: Early-life adversities have a sustained effect on the HPA axis through epigenetic processes and this effect may be measured in peripheral blood. This enduring biological impact of early trauma may alter the development of the brain and lead to adult psychopathological disorder.